2017
DOI: 10.1093/trstmh/trx035
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention for screening detected rheumatic heart disease: opportunities to improve adherence

Abstract: We identified several factors influencing secondary prevention that may be used to develop interventions to improve adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A very low overall adherence of 6% was also reported in the South Pacific nation. 23 Furthermore, different studies reported reasons for poor adherence were lack of money, far distance from hospital, fear of medication side effects and painful injection, lack of awareness of the importance of BPG, and non-availability of BPG. 15,24,25 On the contrary, the adherence rate of the present study (80.6%) was less than that of Indian and New Zealand studies which reported (89.6%) 26 and (92%) 27 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very low overall adherence of 6% was also reported in the South Pacific nation. 23 Furthermore, different studies reported reasons for poor adherence were lack of money, far distance from hospital, fear of medication side effects and painful injection, lack of awareness of the importance of BPG, and non-availability of BPG. 15,24,25 On the contrary, the adherence rate of the present study (80.6%) was less than that of Indian and New Zealand studies which reported (89.6%) 26 and (92%) 27 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…13 Besides this, a study in Fiji reported lack of awareness, feeling well, access and transport cost as determinants of missing of BPG doses by recommending reminder strategies, particularly phone-based reminders which were considered helpful by 94% of participants to improve adherence. 23 Patients shall be advised about the importance of monthly BPG injection and its adherence. Since there were no many alternative drugs for secondary prevention of ARF, the hospital should always avail BPG.…”
Section: Discussionmentioning
confidence: 99%
“…In New Zealand, dedicated RHD-nurses and engaged community health workers results in high adherence rates [25], an approach that has also resulted in highly adherent pediatric patients in some parts of Uganda [21]. Leveraging technology could also play a pivotal role, with young people in Fiji identifying mobile phone reminders as the most useful form of healthcare follow-up [26]. Ongoing work in Uganda through the American Heart Association's Strategically Focused Research Networks [27] to provide national data on the health-system response to RHD may provide additional interventions to improve adherence in this context.…”
Section: Discussionmentioning
confidence: 99%
“…There is an inevitable potential for systematic reviews to become outdated rapidly with the publication of new studies. Since the publication of the review by Kevat et al ., more than ten additional pertinent studies have been published, from Australia [ 11 - 13 ], Egypt [ 14 ], Fiji [ 15 , 16 ], India [ 17 ], Jamaica [ 18 ], New Zealand [ 19 , 20 ], Uganda [ 21 ] and Zambia [ 22 ].…”
Section: Commentmentioning
confidence: 99%
“…Firstly, the findings underscore that the determinants of effective SP implementation arise at the interface of health systems and the patient milieu. Examples of factors repeatedly identified as influencing adherence include geographic remoteness and physical distance to health facilities vis-à-vis transport options [ 15 , 18 , 23 , 24 ], inconvenience to patients exacerbated by competing priorities (such as schooling or employment) and clinic wait times [ 14 , 18 ], the quality of provider-patient relationships and communications [ 23 , 25 - 27 ], fear of painful injections [ 18 , 19 , 28 ], the degree of education and disease awareness among patients (or, in the case of children, their parents) [ 14 , 19 , 27 , 28 ], and levels of support from family and friends [ 24 , 25 ].…”
Section: Commentmentioning
confidence: 99%